Knowledge, Opinions and Attitudes of Italian Mothers towards HPV Vaccination and Pap test. Issue 3 (May 2015) - La Torre, Giuseppe; De Vito, Elisabetta; Ficarra, Maria Giovanna; Firenze, Alberto; Gregorio, Pasquale; Miccoli, Silvia; Giraldi, Guglielmo; Unim, Brigid; De Belvis, Giulio; Boccia, Antonio; ,
Aim: This study evaluated the knowledge and attitudes of Italian mothers – whose daughters had been vaccinated in 2012 – towards primary (anti-HPV vaccination) and secondary (Pap test screening) cervical cancer prevention, as well as sources of information and mother-daughter communication on health issues. Methods: The survey – part of a multicenter study carried out in 4 Italian cities (Ferrara, Rome, Cassino and Palermo) – was conducted through self-administered questionnaires. The first univariate analysis evaluated differences between mothers of under-18s and over-18s relative to knowledge and attitudes on HPV vaccination and Pap test. The second univariate analysis evaluated differences between the 2 groups of mothers and possible geographical variations regarding the sources of information on HPV and Pap test. Results: The sample proved knowledgeable about the correlation between HPV and cervical cancer (>85%) but less aware of other HPV-related diseases. HPV vaccination should be administered before first sexual intercourse according to mothers of over-18s, and to 14- to 17-year-olds according to mothers of under-18s. Up to 88% of mothers of under-18s and 80% of mothers of over-18s declared that the vaccine should be given free of charge. More mothers of under-18s consulted a general practitioner (GP) or gynecologist before deciding to vaccinate their daughters. Mothers of under-18s received information on HPV vaccination mainly from GPs and gynecologists, while mothers of over-18s were informed through TV and books/journals. Over 80% of the sample declared satisfaction with the information received from their gynecologist during the Pap test. Conclusions: The findings provide useful information for the development of effective public health interventions that may help improve acceptance of HPV vaccination among mothers.